Penilaian Strategic Alignment Model (SAM) dan Pemetaan Kerangka Kerja COBIT 4.1 pada PT. XYZ - Fransiska Prihatini Sihotang (Ikatan Ahli Informatika Indonesia (IAII), 2017)
PT. XYZ is a manufacturing company that produces Type I Portland cement and Portland Composite Cement. PT. XYZ has used IS/IT to support its business processes, but does not know the alignment model between IS/IT that has been used against the company's business strategy. PT. XYZ also does not know the maturity level of the application of the IS/IT. This is because there has never been an assessment of the alignment of IS/IT strategy to business strategy and has never done the maturity level measurement from the application of IS/IT. Measurement of the maturity level of application of IS/IT can be done if it is known what processes should be measured. For that reason, mapping is required using a specific framework. Assessment of alignment of IS/IT strategy to business strategy at PT. XYZ uses Strategic Alignment Model (SAM), while to know the process to be measured maturity level used framework COBIT 4.1. The result of this research is known the alignment model of IS/IT strategy to business strategy and IS/IT process which can be measured maturity level in the next step.